2008
DOI: 10.1590/s0101-31222008000300005
|View full text |Cite
|
Sign up to set email alerts
|

Duração do teste de germinação de Brachiaria brizantha cv. marandu (Hochst. ex A. Rich.) Stapf

Abstract: O presente trabalho objetivou determinar o tempo mínimo necessário à realização do teste de germinação para sementes de B. brizantha cv. Marandu, o método de superação de dormência e a condição de temperatura que proporcionem a maior germinação no menor tempo. Numa primeira etapa, realizou-se o teste de germinação em trinta lotes de sementes, sob duas condições de temperaturas (15-35ºC e 20-35ºC), avaliadas em conjunto com três métodos para a superação de dormência (H2SO4, KNO3 e Controle), constituindo seis t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 10 publications
1
6
0
2
Order By: Relevance
“…Thus, we can reduce the evaluation time prescribed by Brasil (2009), in which the first count is made after four days and the final count after 14 days. The possibility of reducing the germination test duration was also observed for Brachiaria brizantha cultivar Marandu (Gaspar-Oliveira et al, 2008) and for Tanzania grass (Tomaz et al, 2010), similarly to that observed in the present study. Figure 3 -Distribution of the relative frequency of Carthamus tinctorius seed germination from lot 5 on substrates between sand, on paper, between paper, and paper roll.…”
Section: Characteristicssupporting
confidence: 90%
See 1 more Smart Citation
“…Thus, we can reduce the evaluation time prescribed by Brasil (2009), in which the first count is made after four days and the final count after 14 days. The possibility of reducing the germination test duration was also observed for Brachiaria brizantha cultivar Marandu (Gaspar-Oliveira et al, 2008) and for Tanzania grass (Tomaz et al, 2010), similarly to that observed in the present study. Figure 3 -Distribution of the relative frequency of Carthamus tinctorius seed germination from lot 5 on substrates between sand, on paper, between paper, and paper roll.…”
Section: Characteristicssupporting
confidence: 90%
“…The standards and procedures of the Rules for Seed Analysis (Brasil, 2009) are periodically reviewed by a committee of researchers and practitioners, but modifications can only be made based on research results (Tomaz et al, 2016). Research on this matter was conducted with forage turnip (Nery et al, 2009), brachiaria grass (Gaspar-Oliveira et al, 2008), and humidicola grass (Tomaz et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…De modo geral, o uso da escarificação química proporcionou uma rápida germinação das sementes pois, aos sete dias, 88% das sementes escarificadas (viáveis) estavam germinados; em contrapartida, somente 40% das sementes sem escarificação (viáveis) haviam germinado; ainda se salienta que quase a totalidade das sementes germinou por volta dos 14 dias. Gaspar- Oliveira et al (2008) verificaram que os tratamentos de escarificação com H 2 SO 4 e a temperatura de 20-35 °C resultaram na maior germinação em menor tempo, possibilitando o encerramento do teste de sementes de B. brizantha cv. Marandu aos 11 dias após a semeadura.…”
Section: Resultsunclassified
“…Although B. brizantha seeds are sometimes dormant (BRASIL, 2009) this has not been observed nowadays in commercial lots of seeds of this species, this being probably due to the fact that the harvested seeds are those which have naturally fallen from the plant and are swept to 575 Evaluation the physiological… SILVA, G. Z. et al be collected, or, in other words, only the physiologically mature seeds are harvested, that is, the seeds which have had the time to complete the maturation process (MASCHIETTO et al, 2003;GASPAR-OLIVEIRA et al, 2008;TOMAZ et al, 2015). Seedling emergence in the field data were used as a reference for the selection of the vigor tests.…”
Section: Resultsmentioning
confidence: 99%